Landslide susceptibility assessment in the Rif-Tell orogenic belt region (NW Africa) from a PGA, PGV and AI probabilistic seismic hazard analysis - Peláez, J.A.; Hamdache, M.; Galindo-Zaldívar, J.; Henares, J.; Delgado, J. (Soil dynamics and earthquake engineering (1984), 2025)
Seismically induced landslides are probably the major side effect of earthquakes. Assessing the occurrence of such events is, therefore, necessary to predict and limit the loss of life and infrastructure, even in regions with moderate seismicity and seismic hazard. The Rif–Tell orogenic region, located in the northwesternmost part of Africa, is subject to moderate seismic activity; however, devastating earthquakes (both historical and instrumental) have occurred in the region. Despite this, and although some studies have focused on particular instances of landslides induced by major events, no general studies on susceptibility to such induced events have been conducted in the region to date. This large-scale landslide susceptibility study we conducted is the first for this region. The study was based on an initial probabilistic seismic hazard assessment in terms of peak ground horizontal acceleration, peak ground horizontal velocity, and horizontal Arias intensity. This methodology facilitates working with a homogeneous dataset of seismic hazard values, everything that is possible, based on the same seismic catalog, seismogenic models, and ground motion prediction models. We conducted a landslide susceptibility assessment using the seismic hazard values and employing the well-known Newmark method. In all considered cases, higher Newmark displacement values were obtained in the central part of Algeria that presents higher susceptibility to such a process. For instance, results in the Chlef region, which was subjected to the notable El Asnam earthquakes in 1950 and 1980, show values above 15 cm for Newmark displacement for a critical acceleration equal to 0.02 g, and above 5 cm for 0.10 g. However, further smaller-scale studies are required to obtain more detailed local results. •The Rif-Tell orogenic area is the region with highest seismic hazard in NW Africa.•Seismic hazard study in terms of PGA, PGV and AI is conducted for the first time in the region.•Landslide susceptibility assessment at regional scale is performed from the Newmark method.•A susceptibility map is presented using seismic hazard values for a 475-yr return period.•The Chlef region (Algeria) stands out with the highest seismic hazard and susceptibility.